Percutaneous intervention for an occluded left Cabrol graft. Issue 6 (December 2019) - Fukuda, Keisuke
Abstract: Percutaneous intervention for surgical reconstruction of a coronary artery is a challenging and complex procedure for interventional cardiologists. Particularly in settings of acute coronary syndrome, urgent revascularization may be critical for the prognosis of patients. Therefore, it is important that physicians have knowledge of various surgical techniques for coronary reconstruction. The Cabrol procedure is one of the surgical techniques after aortic root replacement, but it is rarely used at present. Here we describe a case of successful percutaneous revascularization for an occluded left Cabrol graft in acute ST-elevation myocardial infarction with cardiogenic shock. <Learning objective: Percutaneous intervention for surgical reconstruction of coronary artery is challenging. In coronary artery reconstruction, computed tomography angiography might be extremely useful. We describe a case of successful percutaneous revascularization for the occluded left Cabrol graft.>